2000
DOI: 10.1046/j.1471-4159.2000.0751625.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5‐HT2 Receptor Stimulation of Dopamine Release in the Posterior but Not Anterior Nucleus Accumbens of the Rat

Abstract: Abstract:The objective of the present study was to examine the involvement of serotonin 5-HT 2 receptors within the rat nucleus accumbens (Acc) in the regulation of dopamine (DA) release using in vivo microdialysis. Perfusion with the 5-HT 2 agonist (ϩ)-1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI), at concentrations of 25-250 M, through microdialysis probes located in the posterior Acc increased extracellular DA levels to a maximum of 200% of baseline. DOI-induced increases in the extracellular levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 49 publications
0
31
2
Order By: Relevance
“…The possibility that local fluoxetine decreases behavioral depression through a dopaminergic mechanism cannot be discounted (Nestler and Carlezon, 2006), because infusion of either 5-HT or a 5-HT 2 receptor antagonist into the NAc has been shown to increase DA outflow (Bowers et al, 2000;Parsons and Justice, 1993). It is interesting to note that acute and chronic fluoxetine treatment via systemic routes given to naïve (non-depressed) rats produced either no changes (Clark et al, 1996;Guan and McBride, 1988;Koch et al, 2002Koch et al, , 2004 or slight reductions (Clark et al, 1996;Ichikawa et al, 1998;Ichikawa and Meltzer, 1995) in DA outflow in the NAc.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that local fluoxetine decreases behavioral depression through a dopaminergic mechanism cannot be discounted (Nestler and Carlezon, 2006), because infusion of either 5-HT or a 5-HT 2 receptor antagonist into the NAc has been shown to increase DA outflow (Bowers et al, 2000;Parsons and Justice, 1993). It is interesting to note that acute and chronic fluoxetine treatment via systemic routes given to naïve (non-depressed) rats produced either no changes (Clark et al, 1996;Guan and McBride, 1988;Koch et al, 2002Koch et al, , 2004 or slight reductions (Clark et al, 1996;Ichikawa et al, 1998;Ichikawa and Meltzer, 1995) in DA outflow in the NAc.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding to this latter finding, McBride and colleagues found that reverse dialysis of the 5-HT2 receptor agonist DOI increased DA release in the posterior, but not the anterior, NA (Bowers et al, 2000). These studies implicate receptors localized in the NA in the regulation of mesolimbic DA.…”
Section: Mesolimbic Pathwaymentioning
confidence: 87%
“…We now can confirm that the previously observed effect was not uniquely influenced by intermittent access to PF, and in fact, was not influenced by PF at all, since it was also observed in HCR rats fed only chow or daily PF and chow. There is a growing body of evidence to suggest functional interactions between 5-HT and dopamine in the nucleus accumbens (Bowers, et al, 2000;De Deurwaerdere, et al, 2004;Kuroki, et al, 2003;Liegeois, et al, 2002;Yan and Yan, 2001). It is possible, therefore, that the 5-HT/dopamine interaction is reflected by the strong correlation in turnover ratios present in rats without HCR.…”
Section: Discussionmentioning
confidence: 99%